Optical parameters in food and agricultural processing - Mohd Ali, Maimunah; Hashim, Norhashila; Bejo, Siti Khairunniza; Shamsudin, Rosnah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
The non-destructive feature of optical techniques has gained interests for quality assessment of various agricultural produce as well as in food processing technology. The principle and interaction of light with food and agricultural produce provide essential information for quality assessment which promotes non-destructive inspection methods. This review encompasses the determination of optical properties associated with the evaluation of the quality of agricultural produce. The understanding of how light interacts with turbid agricultural produce is also presented, including light characteristics such as absorption and scattering. A brief overview of the estimation and application of the optical parameters in food and agricultural processing are discussed. The problems and implementation of optical parameters as well as its future trend are also included.